Genetic resources in Russia: from collections to bioresource centers - E. K. Khlestkina (Труды по прикладной ботанике, генетике и селекции)
Collections of bioresources and a set of technologies for their conservation, study and practical use are now the basis of bioeconomy, biosafety, and food security. It is the foundation underpinning production chains, leading from basic research to various technological areas and industries.An analysis of the current state and an assessment of the prospects for the development of bioresource collections in the Russian Federation are presented. Regularities of the transformation from genebanks into bioresource centers and the trend towards integration network interaction among the collections of the same type are considered. The observed trends are analyzed in detail employing the case study of the development of plant genetic resources collections. The current tendencies of their management set by Decrees of the President of the Russian Federation No. 44 “On the National Center for Plant Genetic Resources” and No. 45 “On the Interdepartmental Commission on the Formation, Preservation and Use of Plant Genetic Resources Collections” dated February 8, 2022, are discussed.